Implementasi Metode Analytical Hierarchy Process Dan TOPSIS Dalam Sistem Pendukung Keputusan untuk Pembelian Mobil pada Rental Mobil - Dicky Ahmad Rizaldi; Yunita Yunita; Desty Rodiah (Generic, 2020)
Car rental is a business engaged in services that provide car rental services. Car rental owners must be selective in choosing a car to be used as a fleet, because if the car chosen is not right, the rental owner will experience a loss. To solve this kind of problem, a system to support a decision is a solution that can help rental owners according to their wants or needs. One approach that can be used in this case is the Decision Making System using the Analytical Hierarchy Process (AHP) method and the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS). The Analytical Hierarchy Process (AHP) method was used as weighting and the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) as a ranking. Testing to get a fairly good accuracy using the AHP and TOPSIS methods.